Seismic Wave Propagation Simulation in a Poro-elastic Medium Using Spectral Method Elements in MPI-GPU Cluster: Study Case of Anticline Reservoir Trap - Sudarmaji Sudarmaji; Indra Rudianto; Muhammad Kautsar Rahmareza; Yosua Alfontius (Department of Physics, Sebelas Maret University, 2019)
Modeling 2D seismic wave propagation using spectral element method on MPI-GPU clusters has been implemented and can complete the problem of elastic-poro elastic medium model. Free surface boundary conditions and absorption layer will use the CPML method. Seismic wave propagation simulation in hybrid elastic-poroelastic medium has been carried out on hydrocarbon reservoir models with anticline type. In reservoir rocks that have a poro elastic medium, there will be a fast and slow P wave. While in non-reservoir rocks that have elastic medium, only P fast waves is observed. The computation time for an anticline type reservoir model with dimensions of 1 km x 1.5 km using MPI 4 nodes cluster with 48 CPU cores is 3 minutes 48 second.